High-temperature condensation particle counter using a systematically selected dedicated working fluid for automotive applications. Issue 4 (2nd April 2020) - Kupper, Martin; Kraft, Martin; Boies, Adam; Bergmann, Alexander
Abstract: A stable high-temperature condensation particle counter (HTCPC), operating above 170 °C was realized. First a dedicated working fluid was identified in a two-stage process, consisting of a pre-selection based on relevant substance properties and a subsequent experimental evaluation. A prototype for experimental evaluation of the concept was designed and built, supported by CFD simulations considering the properties of the working fluid. The surface tension of the working fluid was measured at different temperatures, revealing higher values than predicted and a specific adhesion to graphite. With a especially developed high-temperature optics module, the proof of principle was verified. Calibration measurements have been performed against an automotive grade CPC. The operation in compliance to the legislative requirements for particle number counters was successfully proven. Copyright © 2020 American Association for Aerosol Research